2009
DOI: 10.1016/j.bbrc.2009.01.177
|View full text |Cite
|
Sign up to set email alerts
|

Membrane targeting of the EF-hand containing calcium-sensing proteins CaBP7 and CaBP8

Abstract: The CaBP family of EF-hand containing small Ca2+-binding proteins have recently emerged as important regulators of multiple targets essential to normal neuronal function in the mammalian central nervous system. Of particular interest are CaBP7 and CaBP8, abundantly expressed brain proteins that exhibit the greatest sequence divergence from other family members. In this study, we have analysed their sub-cellular localisations in a model neuronal (Neuro2A) cell line and show that both proteins exhibit a membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 28 publications
4
45
0
Order By: Relevance
“…Calneurons do not harbor a Nmyristoylation motif and therefore the question arises as to how they can be tethered to the Golgi. While this study was under review it was reported that calneurons contain in their C terminus a transmembrane domain that might be responsible for Golgi targeting of the overexpressed protein (30). It remains, however, elusive how this transmembrane domain can provide a Golgi membrane anchor.…”
Section: Discussionmentioning
confidence: 96%
“…Calneurons do not harbor a Nmyristoylation motif and therefore the question arises as to how they can be tethered to the Golgi. While this study was under review it was reported that calneurons contain in their C terminus a transmembrane domain that might be responsible for Golgi targeting of the overexpressed protein (30). It remains, however, elusive how this transmembrane domain can provide a Golgi membrane anchor.…”
Section: Discussionmentioning
confidence: 96%
“…A major difference compared with calmodulin is the ability of CaBP 1 and 2 and calneurons 1 and 2 to target to specific cellular membranes (McCue et al 2009). CaBP 1 and 2 are amino-terminally myristoylated, which permits localization to the plasma membrane and Golgi apparatus (Haeseleer et al 2000;Haynes et al 2004).…”
Section: Cabp Familymentioning
confidence: 99%
“…The precise amino-terminal sequence to which the myristoyl group is attached is also important in the targeting of these two proteins, as exemplified by the long and short splice isoforms generated from their genes, which show subtle differences in their localization. CaBP1-Long localizes predominantly to the Golgi and also displays some cytosolic localization, whereas CaBP1-Short localizes most prominently to the plasma membrane and to Golgi structures (Haeseleer et al 2000;McCue et al 2009). Alternative splicing of the CaBP1 gene generates athird protein product, caldendrin (Seidenbecher et al 1998).…”
Section: Cabp Familymentioning
confidence: 99%
See 2 more Smart Citations